2014
DOI: 10.5861/ijrse.2014.696
|View full text |Cite
|
Sign up to set email alerts
|

Exploring parental involvement and teachers’ activities in early literacy development

Abstract: Parental involvement has been seen as an integral component in a child's success and the way teachers design their lessons integrate the essentials of literacy. This study explored activities parents undertake to teach their children how to read and the activities teachers design to promote literacy. The activities were correlated with the students' performance in letter-recognition tasks. Results revealed that parents are aware of their roles in literacy development and are implementing activities at home tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
1
2
0
1
Order By: Relevance
“…The results suggest that most of the parents believe they have a role to play in children's reading related activities at home. The results agree with the claim of Tabbada-Rungduin, et. al.…”
Section: Parents' Level Of Construction Regarding Involvement In Chil...supporting
confidence: 92%
“…The results suggest that most of the parents believe they have a role to play in children's reading related activities at home. The results agree with the claim of Tabbada-Rungduin, et. al.…”
Section: Parents' Level Of Construction Regarding Involvement In Chil...supporting
confidence: 92%
“…Nonetheless, Blair (2014) found that middle-and high-income Filipino parents reported high levels of involvement with children's homework and in volunteering for school related tasks. In another study, Filipino parents reported frequently reminding their children of the importance of going to school (Tabbada-Rungduin, Abulon, Fetalvero, & Suatengco, 2014). Many parents in the same study also reported that they believed that they are their children's first teacher, especially in learning how to read.…”
Section: The Filipino Family and Educationmentioning
confidence: 97%
“…In a survey among Grade 2 students, around 70% of mothers and fathers were reported to be literate, approximately 40% of students reported receiving help from their parents with reading at home, and nearly 50% of students reported that they had other books aside from textbooks at home (Education Development Center, ). Parents of 4‐ to 6‐year‐old daycare students in Manila reported high levels of involvement (“almost always practiced”) in school‐related tasks such as attending parent–teacher meetings, asking children about what happened in school, and reminding children of the importance of school; in contrast, storybook reading at home was rated as “sometimes practiced” (Tabbada‐Rungduin, Abulon, Fetalvero, & Suatengco, ). However, parental involvement and children's skills were weakly correlated in this sample.…”
Section: Introductionmentioning
confidence: 99%